2015
DOI: 10.3892/mmr.2015.3926
|View full text |Cite
|
Sign up to set email alerts
|

Berberine induces apoptosis by suppressing the arachidonic acid metabolic pathway in hepatocellular carcinoma

Abstract: Berberine (BBR) has been suggested as a potential candidate anticancer agent due to its high anticancer activity and multiple mechanisms. In the present study, the inhibitory effect of BBR on hepatocellular carcinoma (HCC) via the suppression of the arachidonic acid (AA) metabolic pathway was investigated. BBR was demonstrated to reduce the viabilities of H22, HepG2 and Bel‑7404 cells, in a dose‑ and time‑dependent manner, and increase the number of apoptotic cells. BBR induced the translocation of apoptosis‑i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 28 publications
2
48
0
Order By: Relevance
“…A recent CE-TOFMS-based metabolomics study suggested that the metabolic profile of DEN model is effective to identify novel biomarkers for early diagnosis of human hepatocellular carcinoma (30). Indeed, inhibition of AA metabolic pathway has been recently reported to associate with the chemoprevention of high fat diet-enhanced colorectal carcinogenesis (41) and the apoptosis of hepatocellular carcinoma cells (42). Furthermore, significantly elevated content of AA was also reported in hepatocellular carcinoma patients compared with the healthy controls (11).…”
Section: Discussionmentioning
confidence: 99%
“…A recent CE-TOFMS-based metabolomics study suggested that the metabolic profile of DEN model is effective to identify novel biomarkers for early diagnosis of human hepatocellular carcinoma (30). Indeed, inhibition of AA metabolic pathway has been recently reported to associate with the chemoprevention of high fat diet-enhanced colorectal carcinogenesis (41) and the apoptosis of hepatocellular carcinoma cells (42). Furthermore, significantly elevated content of AA was also reported in hepatocellular carcinoma patients compared with the healthy controls (11).…”
Section: Discussionmentioning
confidence: 99%
“…Induction of apoptosis and tumour growth inhibition both in vitro and in vivo. Li et al [37] T47D and MCF7 cell lines.…”
Section: Cell Type or Animal Modelmentioning
confidence: 99%
“…BBR altered the viability and apoptosis of HCC cells in a dose-dependent fashion by inducing the translocation of apoptosis-inducing factor between the mitochondria and nucleus. BBR suppressed the levels of cytosolic phospholipase A2 (cPLA) and COX2 which increase the ratio of AA to PEG2 [272]. …”
Section: Introductionmentioning
confidence: 99%